Characteristics of interline table watermelon F1 hybrids according to the degrees of dominance and indices of true and hypothetical heterosis - E. A. Varivoda; N. G. Baibakova (Труды по прикладной ботанике, генетике и селекции)
Background. Heterosis is one of the most important and promising plant breeding trends. Its development will make it possible to obtain hybrids with high adaptability and a high heterosis effect in their quantitative and qualitative characteristics.Materials and methods. The studies were carried out under dry conditions of the Volgograd Trans-Volga region in 2019–2020. Heterotic hybrids of table watermelon served as the research material, and hybridization and inbreeding as research methods. The heterotic F1 hybrid of watermelon Barkhan was used as the reference.Results. The characteristics of heterotic watermelon hybrids were compared with the parental forms and the Barkhan F1 reference. The length of the growing season in heterotic hybrids was inherited intermediately. In the average fruit weight, the reference was exceeded by the hybrids ChmsMt and ChmsFt by 1.1 kg. The highest average yield for the two years of research was observed in the F1 hybrids ChmsNts (24.3 t/ha), ChmsFt (24.1) and ChmsMt (23.1) (reference: 20.8 t/ha). The inheritance of fruit weight according to the principle of overdominance occurred in the F1 hybrids ChmsMk, ChmsRn, ChmsNts and ChmsMt. In their fruit weight, the same hybrids showed positive indices of hypothetical and true heterosis. The F1 hybrids ChmsFt, ChmsNts and ChmsIR demonstrated high degrees of dominance in yield (1.8 to 5.0%). The index of hypothetical heterosis had positive results in all studied heterotic watermelon hybrids. Negative true heterosis (–0.49%) was observed in two F1 hybrids, ChmsRn and ChmsPH. The remaining watermelon hybrids had positive true heterosis indices that ranged from 2.4% in ChmsIR to 11.06% in ChmsFt.Conclusion. As a result of the studies, heterotic hybrids of watermelon, developed on the basis of the sterile mother line Chms, were identified for high indices of true and hypothetical heterosis in fruit weight and yield parameters.